Oxidation of tetracycline hydrochloride with a photoenhanced MIL-101(Fe)/g-C3N4/PMS system: Synergetic effects and radical/nonradical pathways - Jianjun Song; Xiaoying Yuan; Meikun Sun; Zuchen Wang; Gege Cao; Kangqi Gao; Chuanxi Yang; Fengmei Zhang; Feng Dang; Weiliang Wang (Ecotoxicology and Environmental Safety, 2023)
MIL-101(Fe)-based catalysts have been widely used for degradation of organic pollutants based on peroxymonosulfate (PMS) activation. Hence, a facile calcination and hydrothermal method was used in this study to prepare a MIL-101(Fe)/g-C3N4 composite catalyst with high activity and high stability for PMS activation to degrade tetracycline hydrochloride (TC) under visible-light irradiation. We clearly elucidated the mechanism involved in the MIL-101(Fe)/g-C3N4 photo Fenton-catalyzed PMS activation process by separating the PMS activation and pollutant oxidation processes. The synergetic effects of MIL-101(Fe) and g-C3N4 involved MIL-101(Fe) acting as an electron shuttle mediating electron transfer from the organic substrate to PMS, accompanied by redox cycling of the surface Fe(II)/Fe(III). Multiple experimental results indicated that PMS was bound to the surface of MIL-101(Fe)/g-C3N4 during visible irradiation and generation of sulfate radicals (SO4•-), hydroxyl radicals (•OH) and superoxide anion free radicals (•O2-) for the radical pathway and singlet oxygen (1O2) and holes (h+) for the nonradical pathway. The major degradation pathways for TC can be described as demethylation, deamination, deamidation and carbonylation. This work provides valuable information and advances the fundamental understanding needed for design and syntheses of metal-free conjugated polymers modified by metal-organic frameworks for heterogeneous photo-Fenton reactions.